Opportunities that Primary and Secondary School Children Get After Parents’ Divorce in Mvomero District Tanzania - Maximillian, Christina; Babune, George Julius (Journal of Advanced Research in English & Education; Vol 9 No 1 (2024): Journal of Advanced Research in English & Education, 2024)
This paper reversed the spectrum by examining whether or not there could be opportunities that children get after parent divorce using the case of primary and secondary school children in Mtibwa and Mkindo wards of Mvomero District Tanzania. The mixed approach was used to generate data using a 149 sample selected purposively. Questionnaire survey and interview data collection methods were employed whereas analysis involved theme and content analysis as well as descriptive statistics. It was found that there are more children whose parents experienced divorce in Madizini village 58 (38.9%) than there are in other villages of whom the majority were female 93 (62.4%). It was found that there were social, institutional and welfare opportunities that children get after their parents divorce. Children benefit from private and public spheres that provide health, and education assistance and protect them from violence. It was found that children enjoyed a better life before their parents divorced compared to the short period after divorce. The majority of children’s life-long period after their parents divorced was better than the divorce onset period. It was concluded that there are opportunities that children have after their parents’ divorce. Attention is called to enhance these opportunities for sustainable children with divorced parents.